The Effect of 6-Week Combined Balance and Plyometric Training on Change of Direction Performance of Elite Badminton Players - Guo, Zhenxiang; Huang, Yan; Zhou, Zhihui; Leng, Bo; Gong, Wangcheng; Cui, Yixiong; Bao, Dapeng (Frontiers in Psychology, 2021)
The aim of this study was to investigate the effect of combined balance and plyometric training on change of direction performance of badminton athletes. Sixteen elite male badminton players volunteered to participate and were randomly assigned to a balance-plyometric group (BP: n=8) and plyometric group (PL: n=8). The BP group performed balance combined with plyometric training three times a week over 6 weeks; while PL group undertook only plyometric training three times a week during the same period. Meanwhile, both groups carried out the same technical training. All participants were tested to assess change of direction ability: (SEMO test and 5-0-5 test), dynamic balance ability (Y-Balance test) and reactive strength index (RSI) before and after the training period. Repeated-measure analysis of variance revealed that after the intervention, there was a significant time × group interaction for 5-0-5 test, Y-Balance test of both legs and RSI (p<0.05, partial η^2=0.26-0.58) due to the better performance observed at post-test compared with pre-test for BP group (effect size [ES]=1.20-1.76), and the improvement was higher than that of PL group. The change in SEMO test did not differ between BP and PL (p<0.159, partial η^2=0.137), but the with-group improvement for BP (ES=1.55) was higher than that of PL (ES=0.81). These findings suggest that combined training could further improved the change of direction performance of badminton athletes than plyometric training alone, and might provide fitness trainers a more efficient change of direction training alternative.